Breastfeeding Intention, Knowledge, and Attitude of Pregnant Women in Treatment for Opioid Use Disorder - Short, Vanessa L.; Abatemarco, Diane J.; Gannon, Meghan (American Journal of Perinatology, 2021)
Objective The objective of this study was to describe breastfeeding intention, knowledge, and attitude, and sources of infant feeding information during the prenatal period among a cohort of pregnant women in treatment for opioid use disorder (OUD).Study Design Pregnant women who were receiving treatment for OUD and in the third trimester completed a questionnaire that measured demographic characteristics, infant feeding intentions, breastfeeding beliefs and attitudes, and sources of breastfeeding information. Frequency counts and percentages and means and standard deviations were used to describe data.Results Sixty-five women completed the survey. Three-fourths reported some intention to breastfeeding. While attitudes around breastfeeding were generally positive, less than half of respondents knew the recommendations and infant health benefits of breastfeeding.Conclusion Prenatal programs for women in treatment for OUD should consider addressing patient-reported concerns and gaps in knowledge regarding the benefits of and recommendation for breastfeeding.Key Points
Keywords: breastfeeding; intention; knowledge; opioid use disorder; pregnancy; survey